1975
DOI: 10.1515/znc-1975-7-804
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Lignin from Soybean Cell Suspension Cultures

Abstract: yielded two substances which gave a yellow color with 2,4-dinitrophenylhydrazine and had the same Rp-values as p-hydroxybenzaldehyde and v an illin7. The insoluble residue could therefore be described as lignin-like m aterial. In view of the above men tioned work on the enzymology of lignin biosynthe sis in the soybean cell cultures it was, however, necessary to obtain more precise inform ation on the structure of the lignin formed by the cell cul tures. Since 13C-NMR-spectroscopy has been shown to be a valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…However, nitrate starvation does not result in the stimulation of a general increase in the activities of all of the enzymes involved in phenylpropanoid metabolism. Three enzymes presumably involved in lignin biosynthesis (6), an 0-methyltransferase and two cinnamoyl CoA ester reductases, do not vary in specific activity during the entire growth cycle of a soybean cell suspension culture, although lignin can be detected in these cultures (26).…”
Section: Resultsmentioning
confidence: 99%
“…However, nitrate starvation does not result in the stimulation of a general increase in the activities of all of the enzymes involved in phenylpropanoid metabolism. Three enzymes presumably involved in lignin biosynthesis (6), an 0-methyltransferase and two cinnamoyl CoA ester reductases, do not vary in specific activity during the entire growth cycle of a soybean cell suspension culture, although lignin can be detected in these cultures (26).…”
Section: Resultsmentioning
confidence: 99%
“…Microanalytical and autoradiographic studies have indicated that the deposition of H units typifies the early developmental stages of lignification occurring in the middle lamella (Whiting and Goring, 1982;Sorvari et al, 1986;Terashima and Fukushima, 1988;Fukushima and Terashima, 1990). in a11 cases in which it has been examined, an elevated content of H units has also been observed for lignins formed de novo in cell culture systems (Glycine: Nimz et al, 1975;Rosa: Mollard and Robert, 1983;Pinus: Fukuda et al, 1988, Campbell and Ellis, 1992, Eberhardt et al, 1993Picea: Brunow et al, 1993;Camellia: Zaprometov et al, 1993), and it has frequently been observed in intact plants challenged with pathogens (Rapkanus: Asada and Matsumoto, 1972;Triticum: Ride, 1975;Cucurbita sp. : Hammerschmidt et al, 1985; Prunus: Doster and Bostock, 1988;Cucumis: Robertsen and Svalheim, 1990).…”
Section: Lignin Subunit Compositionmentioning
confidence: 99%
“…In addition to lignin biosynthesis, the phenylpropanoid pathway is used in the synthesis of a vast array of phenolic compounds including phytoalexins, phenylpropanoid conjugates and flavonoids (Dixon et al, 2002 ; Ahuja et al, 2012 ; Großkinsky et al, 2012 ; Cho and Lee, 2015 ). Hydroxycinnamoyl-CoA esters are subsequently channeled into the lignin branch pathway to produce monolignols through hydroxycinnamaldehydes via two reductive steps catalyzed by CCR and cinnamyl alcohol dehydrogenase (Nimz et al, 1975 ; Gross, 1981 ; Lüderitz and Grisebach, 1981 ; Lacombe et al, 1997 ). In addition to serving as intermediates in lignin biosynthesis, hydroxycinnamaldehydes, and monolignols can play a role as defensive compounds and act as precursors for lignan biosynthesis (Keen and Littlefield, 1979 ; Barber et al, 2000 ; Davin et al, 2008 ; König et al, 2014 ; Satake et al, 2015 ; Teponno et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%